Size-mediated response to public cues of predation risk in a tropical stream fish - Elvidge, C. K.; Ramnarine, I. W.; Godin, J.-G. J.; Brown, G. E. (Journal of fish biology, 2010)
In order to investigate any size‐dependent differences between behavioural patterns, wild‐caught Hart's rivulus Rivulus hartii of varying sizes were exposed to chemical alarm cues extracted from the skin of conspecifics or heterospecific Poecilia reticulata, or a tank water control, in a series of laboratory trials. In response to conspecific alarm cues, R. hartii subjects of the range of body sizes tested exhibited consistent, size‐independent antipredator behaviours that were characterized by decreased locomotory activity and foraging levels and increased refuging behaviour. Conversely, focal R. hartii demonstrated significant size‐dependent trends in response to heterospecific alarm cues, with smaller individuals exhibiting antipredator responses and larger individuals shifting their behaviour to increased levels of activity consistent with a foraging, or predatory, response. These results show that the behavioural responses of individual R. hartii to publicly available chemical alarm cues from heterospecifics are mediated by the size of the receiver.